2004
DOI: 10.1158/1078-0432.ccr-04-0958
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inhibitor of Nuclear Factor-κB Phosphorylation Increases the Efficacy of Paclitaxel in in Vitro and in Vivo Ovarian Cancer Models

Abstract: We investigated whether inhibition of nuclear factor-B (NF B) increases the efficacy of paclitaxel in in vitro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
137
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 51 publications
8
137
1
Order By: Relevance
“…In relation to these data, PS-341 has been administrated alone or in combination to other drugs in multiple myeloma patients, refractory to conventional therapies [19]. Similar results obtained with other NF-kB inhibitors have been described in ovarian cancer [20], in acute myeloid leukemia [8], and in other neoplasia. In line with these data, we have shown that NF-kB inhibition may be a strategy to increase sensitivity to Etoposide-induced apoptosis in a cell line derived from a CML blast crisis.…”
Section: Discussionmentioning
confidence: 59%
“…In relation to these data, PS-341 has been administrated alone or in combination to other drugs in multiple myeloma patients, refractory to conventional therapies [19]. Similar results obtained with other NF-kB inhibitors have been described in ovarian cancer [20], in acute myeloid leukemia [8], and in other neoplasia. In line with these data, we have shown that NF-kB inhibition may be a strategy to increase sensitivity to Etoposide-induced apoptosis in a cell line derived from a CML blast crisis.…”
Section: Discussionmentioning
confidence: 59%
“…Although the molecular basis of resistance to Taxol is not well-documented, mounting evidence supports the role of intrinsically or constitutively activated nuclear factor-κB (NF-κB) in affording protection against programmed cell death. Constitutive high levels of NF-κB activity have been detected in response to chemotherapy and radiation in ovarian cancer (3)(4)(5), pancreatic cancer (6), breast cancer (7,8), and prostate cancer (9). Our recent work has revealed that nuclear RelA and cytoplasmic pI-κBα are significantly associated with a poor prognosis in cancer (10).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a broad array of actions independent of DNA adduct production has been described, including activation of mitochondrial (Biroccio et al, 2004) and Fas-associated apoptotic pathways (Razzaque et al, 1999) as well as induction of mitogen-activated protein kinases (MAPKs) (Zhang et al, 2005;Villedieu et al, 2006). Moreover, anti-invasive properties of cisplatin have been reported (Morikawa et al, 1995;Mabuchi et al, 2004) with the underlying mechanisms still being poorly understood.…”
mentioning
confidence: 99%